Bercerita Dan Pembiasaan: Metode Penguatan Nilai Multikultural Di Madrasah: Storytelling and Habituation: Methods for Strengthening Multicultural Values in Madrasah - Imam Bukhari (Fenomena, 2017)
The phenomenon of Indonesia's multi-ethnic, religious, and cultural society has the potential to generate conflict if values of togetherness are not instilled from an early age. Multicultural education becomes a crucial strategy for building social cohesion, especially in Islamic elementary schools. This study aims to describe the methods of instilling multicultural values and their impact on student behavior. This descriptive qualitative study was conducted in four madrasahs in Kraksaan District through observation, interviews, and documentation, with inductive data analysis. The findings reveal that the most frequently used methods are storytelling and behavioral habituation. Both methods effectively transform students' attitudes from rejecting differences to being more tolerant and appreciative of peers from diverse backgrounds. However, the main obstacles faced by teachers include a lack of mastery of storytelling techniques, limited media, and inconsistencies between values taught at school and habits at home and in the community. In conclusion, strengthening multicultural values through storytelling and habituation positively influences students' behavioral changes. It is recommended to enhance teachers' storytelling competencies, provide learning media, and strengthen partnerships with parents to create value consistency. Fenomena masyarakat Indonesia yang majemuk secara etnis, agama, dan budaya berpotensi menimbulkan konflik jika nilai-nilai kebersamaan tidak ditanamkan sejak dini. Pendidikan multikultural menjadi strategi penting untuk membangun kohesi sosial, terutama di madrasah ibtidaiyah. Penelitian ini bertujuan mendeskripsikan metode penanaman nilai multikultural serta dampaknya terhadap perilaku siswa. Studi kualitatif deskriptif ini dilakukan di empat madrasah di Kecamatan Kota Kraksaan melalui observasi, wawancara, dan dokumentasi, dengan analisis data secara induktif. Hasil penelitian menunjukkan bahwa metode yang paling sering digunakan adalah bercerita dan pembiasaan perilaku. Kedua metode ini terbukti efektif mengubah sikap siswa dari tidak menerima perbedaan menjadi lebih toleran dan menghargai teman yang berbeda latar belakang. Namun, kendala utama yang dihadapi guru adalah kurangnya penguasaan teknik bercerita dan keterbatasan media, serta inkonsistensi antara nilai yang diajarkan di sekolah dengan kebiasaan di rumah dan lingkungan masyarakat. Kesimpulannya, penguatan nilai multikultural melalui bercerita dan pembiasaan berdampak positif pada perubahan perilaku siswa. Direkomendasikan peningkatan kompetensi guru dalam metode bercerita, penyediaan media pembelajaran, serta penguatan kemitraan dengan orang tua untuk menciptakan konsistensi nilai.